Systemic versus local responses in melanoma patients treated with talimogene laherparepvec from a multi-institutional phase II study. Issue 1 (December 2016) - Kaufman, Howard; Amatruda, Thomas; Reid, Tony; Gonzalez, Rene; Glaspy, John; Whitman, Eric; Harrington, Kevin; Nemunaitis, John; Zloza, Andrew; Wolf, Michael; Senzer, Neil
Abstract Background We previously reported that talimogene laherparepvec, an oncolytic herpes virus encoding granulocyte-macrophage colony-stimulating factor (GM-CSF), resulted in an objective response rate of 26 % in patients with advanced melanoma in a phase II clinical trial. The response of individual lesions, however, was not reported. Since talimogene laherparepvec is thought to mediate anti-tumor activity through both direct tumor cytolysis and induction of systemic tumor-specific immunity, we sought to determine the independent response rate in virus-injected and non-injected lesions. Methods Fifty patients with stage IIIC or IV melanoma were treated with talimogene laherparepvec in a multi-institutional single-arm open-label phase II clinical trial. In this study patients were treated until a complete response was achieved, all accessible tumors disappeared, clinically significant disease progression, or unacceptable toxicity. This report is a post hoc analysis of the systemic effects of talimogene laherparepvec in injected lesions and two types of uninjected lesions—non-visceral lesions and visceral lesions. Results Eleven of 23 patients (47.8 %) had a ≥ 30 % reduction in the total burden of uninjected non-visceral lesions, and 2 of 12 patients (16.7 %) had a ≥ 30 % reduction in the total burden of visceral lesions. Among 128 evaluable lesions directly injected with talimogene laherparepvec, 86 (67.2 %) decreased in size by ≥ 30 % and 59 (46.1 %) completely resolved. Of 146 uninjected non-visceral lesions, 60 (41.1 %) decreased in size by ≥ 30 %, the majority of which (44 [30.1 %]) completely resolved. Of 32 visceral lesions, 4 (12.5 %) decreased in size by ≥ 30 %, and 3 (9.4 %) completely resolved. The median time to lesion response was shortest for lesions that were directly injected (18.4 weeks), followed by uninjected non-visceral lesions (23.1 weeks) and visceral lesions (51.3 weeks), consistent with initiation of a delayed regional and systemic anti-tumor immune response to talimogene laherparepvec. Conclusions These results support a regional and systemic effect of talimogene laherparepvec immunotherapy in patients with advanced melanoma.